2013
DOI: 10.1093/icvts/ivt280
|View full text |Cite
|
Sign up to set email alerts
|

Late coronary artery and tricuspid valve injury post pectus excavatum surgery

Abstract: We report the surgical case of a 25-year old man admitted because of progressive dyspnoea and stabbing chest pain, who had undergone a pectus excavatum correction using a retrosternal strut 8 years previously. The computerized tomography scan showed that the right tip of the pectus bar had migrated across his right ventricle and tricuspid valve into the right atrium. Intraoperatively, it was confirmed that in its path, the right coronary artery and the posterior leaflet of the tricuspid valve had been damaged.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A failed STRATOS implant also brings the danger of loose and migrating long pieces of metal with sharp ends in the cardiothoracic region (Fig 2a, b) with its vital blood carrying vessels and organs like heart and lung. A recent study reported migration of a pectus bar through the tricuspid valve into the right atrium of the heart, damaging the right coronary artery and posterior leaflet of the tricuspid valve on the way [10].…”
Section: Commentmentioning
confidence: 99%
“…A failed STRATOS implant also brings the danger of loose and migrating long pieces of metal with sharp ends in the cardiothoracic region (Fig 2a, b) with its vital blood carrying vessels and organs like heart and lung. A recent study reported migration of a pectus bar through the tricuspid valve into the right atrium of the heart, damaging the right coronary artery and posterior leaflet of the tricuspid valve on the way [10].…”
Section: Commentmentioning
confidence: 99%
“…Cardiopulmonary ByPass patients sustained intracardiac bar migration from two to 37 years after the initial procedure as a consequence of failure to remove the bar in a timely manner and/or broken material[17][18][19][20]. Injured cardiac structures are detailed in Table1.…”
mentioning
confidence: 99%